Rat Mesenchymal Stromal Cells Inhibit T Cell Proliferation but Not Cytokine Production Through Inducible Nitric Oxide Synthase - Zinöcker, Severin; Vaage, John T. (Frontiers in Immunology, 2012)
Mesenchymal stromal cells (MSC) have important immunomodulatory properties, they inhibit T lymphocyte allo-activation and have been used to treat graft-versus-host disease. How MSC exert their immunosuppressive functions is not completely understood but species specific mechanisms have been implicated. In this study we have investigated the mechanisms for rat MSC mediated inhibition of T lymphocyte proliferation and secretion of inflammatory cytokines in response to allogeneic and mitogenic stimuli in vitro. MSC inhibited the proliferation of T cells in allogeneic mixed lymphocyte reactions and in response to mitogen with similar efficacy. The anti-proliferative effect was mediated by the induced expression of nitric oxide (NO) synthase and production of NO by MSC. This pathway was required and sufficient to fully suppress lymphocyte proliferation and depended on proximity of MSC and target cells. Expression of inducible NO synthase by MSC was induced through synergistic stimulation with tumor necrosis factor α and interferon γ secreted by activated lymphocytes. Conversely, MSC had a pronounced inhibitory effect on the secretion of these cytokines by T cells which did not depend on NO synthase activity or cell contact, but was partially reversed by addition of the cyclooxygenase (COX) inhibitor indomethacin. In conclusion, rat MSC use different mechanisms to inhibit proliferative and inflammatory responses of activated T cells. While proliferation is suppressed by production of NO, cytokine secretion appears to be impaired at least in part by COX-dependent production of prostaglandin E2.